Analisis Penerapan Inkuiri Secara Daring dengan Scaffolding Berbantuan Geogebra Materi Fungsi Kuadrat - Nurul Mufidha; Subanji Subanji (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This study aims to analyze and describe the application of online inquiry learning with the GeoGebra-assisted scaffolding technique on quadratic function material in grade IX students at SMP Negeri 1 Malang. This research is a qualitative descriptive study, with the instruments used in the form of a learning implementation sheet, student activity sheets, student learning outcomes tests, questionnaires, and interviews. The results showed that learning according to the steps of inquiry had gone very well with an average implementation score of 94.5. Learning is carried out by scaffolding through questions directed at focusing, inviting, reminding, clarifying, and evaluating so that it is compatible with inquiry learning which is applied online. Student learning outcomes reached an average score of 73 daily tests in the good category.